Differences in Responsible Environmental Behavior based on Gender and Level of Knowledge about Waste Issues in Generation Z in Yogyakarta Province - Hanafi, Yahya; Hasanah, Uswatun; Budiaman, B (Universitas Muhammadiyah Surakarta, 2025)
Environmental issues related to waste are current global, national, and local. Waste is the number one priority environmental issue in DI Yogyakarta. The Generation Z group dominates the population in Indonesia and DI Yogyakarta. This study aims to analyse the differences in the REB of Gen Z based on gender, the differences in REB of Gen Z based on the level of knowledge about waste issues, and the interaction between gender and level of knowledge on REB of Gen Z. The type of research is quantitative, using a survey method. The variables used in the study are responsible environmental behaviour, knowledge about waste issues, and situational factors (gender). The data collection was carried out in January-February 2025. The research location is SMP Negeri 1 Banguntapan, Bantul, and SMA Negeri 2 Banguntapan, Bantul. The research respondents were 110 students of SMP Negeri 1 Banguntapan and 130 students of SMA Negeri 2 Banguntapan. Data analysis techniques include descriptive and inferential statistics with two-way ANOVA. The results of the hypothesis test for the gender variable are 0,052 > 0,05, so it can be concluded that there is no significant difference in gender in Gen Z REB. The hypothesis test for the variable level of knowledge about the issue of waste showed 0,00 < 0,05, and it can be concluded that there is a significant difference in the level of knowledge about the issue of waste among Gen Z REB. The hypothesis test for the interaction between the variable level of knowledge about the issue of waste and gender is 0,089 > 0,05, so it can be concluded that there is no interaction between gender and the level of knowledge about the issue of waste.